2022
DOI: 10.3389/fmicb.2022.908981
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic microbial consortia derived from rhizosphere soil protect wheat against a soilborne fungal pathogen

Abstract: Synthetic microbial communities (SynComs) could potentially enhance some functions of the plant microbiome and emerge as a promising inoculant for improving crop performance. Here, we characterized a collection of bacteria, previously isolated from the wheat rhizosphere, for their antifungal activity against soilborne fungal pathogens. Ten SynComs with different compositions from 14 bacterial strains were created. Seven SynComs protected wheat from Rhizoctonia solani AG8 infection, although SynComs were not mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 93 publications
1
5
0
Order By: Relevance
“…On the other hand, the microbial consortium often shows a lesser effect, as observed in this study, which may indicate the prevalence of antagonistic interactions over the best-performing single or a few beneficial bacterial isolates. Therefore, the combination of effective strains with better stability of similar genera and additive effects on plant growth promotion often termed synthetic microbial communities (e.g., SynComs), becomes more robust and is increasingly recognized in modern agriculture (Yin et al, 2022). In this line of evidence, our results strongly encourage the development of an effective biofertilizer derived from these two reported bacteria and a few more similarly effective isolates in the near future.…”
Section: The Plant Biostimulant Potential Of Kunapajala and Modes Of ...supporting
confidence: 60%
“…On the other hand, the microbial consortium often shows a lesser effect, as observed in this study, which may indicate the prevalence of antagonistic interactions over the best-performing single or a few beneficial bacterial isolates. Therefore, the combination of effective strains with better stability of similar genera and additive effects on plant growth promotion often termed synthetic microbial communities (e.g., SynComs), becomes more robust and is increasingly recognized in modern agriculture (Yin et al, 2022). In this line of evidence, our results strongly encourage the development of an effective biofertilizer derived from these two reported bacteria and a few more similarly effective isolates in the near future.…”
Section: The Plant Biostimulant Potential Of Kunapajala and Modes Of ...supporting
confidence: 60%
“…Although the most convenient method could have been the individual treatment by strain, we considered that a small consortium in the synthetic community made more sense to cover most of the required skills, which no single strain seemed capable of covering. This approach has provided more promising results in complex systems, such as our object of study, as we can find in the studies by Schmitz et al, Yin et al, and Flores-Duarte et al [ 78 , 103 , 104 ]. Apart from the improvements described before in the germination and development of the B. bituminosa seedlings, this treatment showed that it was able to improve the degree of aggregation, something that we verified both through the Slaking index, as well as by granulometry ( Figure 6 and Figure 7 ).…”
Section: Discussionmentioning
confidence: 91%
“…In vitro experiments, it was observed that R. erythropolis B43 reduced wheat root rot caused by Rhizoctonia solani AG8. This bacterium can produce volatile substances that inhibit the growth of R. solani AG8 (Yin et al 2022). Other bacterial strains have been reported to be effective in controlling the root rot of wheat due to B. sorokiniana.…”
Section: Discussionmentioning
confidence: 99%